A conceptual framework for platform-based design of non-assembled products. (December 2017) - Lager, Thomas
Abstract: In this study, the use of platform-based product family design of assembled products has been reconceptualised into a framework of platform-based design of non-assembled products for the process industries. As a point of departure, platform-based design is defined as shared logic in a company's activities, and a "function-based" leveraging strategy is employed to identify non-assembled products with similar characteristics and commonalities among product families, related production processes and raw materials. It is proposed that a production platform philosophy and platform-based design of non-assembled products should rely on Product platforms, Process platforms and Raw-material platforms that are well-integrated into common Production platforms, in an end-to-end perspective. However, platform-based design of non-assembled products may differ depending on whether company production relies solely on a captive raw material base or on purchased raw materials on the open market, or on both. The congruence of the development of Production platforms with the QFD methodology and House of Quality was noted in this study, as well as the simplicity of using the methodology on homogeneous products compared to multi-level hierarchical assembled products. It is argued that the proposed conceptual framework can be used in internal company discussions and reviews whether and how such an approach in product innovation can be a fruitful avenue to explore and adapt. Highlights: ● Based on a review of the platform based product family design of assembled products and the conditions for process-industrial product innovation, a conceptual framework has been developed for a production platform philosophy and platform-based design of non-assembled products. However, the use of the philosophy of platform-based design or non-assembled products in the process industries must, in a similar vein to platform-based product family design of assembled products, always and only be driven by a company's desire to adapt a high-variety strategy. ● It is initially concluded that previously presented platform development approaches and definitions for assembled products are not fit-for-purpose for the development of non-assembled products. The following definition, is therefore proposed: A Production platform philosophy for non-assembled products in the process industries involves the identification and exploitation of the shared logics and commonalities of a firm's products, production technologies and raw materials, in order to achieve leveraged product variety and other customer offerings, while maintaining economies of scale and scope of its production capabilities. ● The framework introduces a Production platform philosophy and its inclusive structural components. The components of a Production platform should include a well-integrated Product platform, Process platform and Raw material platform delivering a family of derivate products supplying different market segments, relying on a captive or/and supplied raw material base in an end-to-end perspective. Platform-based design of non-assembled products may differ depending on whether company production solely relies on a captive raw material base or on raw materials purchased on the open market, or both. ● After all individual Customer Requirements for a product family are identified, and their importance ratings within all selected different market segments are assessed, these importance ratings must afterwards be recalculated into importance ratings of all Design Requirements for each individual market segment. A "function-based" product leveraging strategy for platform-based design of non-assembled products is then setting target figures for the conceptual development of each product variety, based on the variability of each individual Design Requirement and commonalities of functional properties within the product family. ● The use of the House of Quality for translation of customer needs and requirements into product design requirements is recommended. The need to integrate process technology and raw material specifications, the use of the QFD phase progression system to transfer product functionalities into process capabilities is advocated. Production platforms for non-assembled products are relying on a firm's shared customer, product, process and raw material knowledge for a selected product family. It is suggested that such a knowledge base be called an Integrated Knowledge Platform.